Pengaruh Sales Growth, Likuiditas, dan Leverage terhadap Tax Avoidance pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode Tahun 2021-2023 - A.Frida Fitriani (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the effect of sales growth, liquidity, and leverage on tax avoidance in food and beverage companies listed on the Indonesia Stock Exchange (BEI) during the period 2021-2023. Using a sample of 10 companies, this research collected financial data and annual reports to evaluate the relationship between these variables. The results of analysis indicate that sales growth and leverage have a significant effect on tax avoidance. Furthermore, the simultaneoustest results how that three variables collectively have a significant effect on tax avoidance. This study provides insights for stakeholders in understanding the dynamics of taxation within this industry and highlights the importance of considering other financial factors that may influence tax avoidance